Understanding Brexit : Why Britain Voted to Leave the European Union. - Taylor, Graham (Emerald Publishing Limited, 2017)
On 23rd June 2016, the United Kingdom shocked the world by voting to leave the European Union. This short book examines why this happened, examining the historical, economic, political, social and cultural reasons that led to the Brexit vote.
Keywords: European Union -- Great Britain.; European Union.; Great Britain -- Foreign relations -- European Union countries.; European Union countries -- Foreign relations -- Great Britain.; Great Britain -- Politics and government -- 2007-; European Union countries.; Great Britain.; Since 2007; elektronické knihy; electronic books